Deanxit and tandospirone relieved unexplained limb edema in a depressed pituitary adenoma survivor: A case report - Dong, Xingyu; Fang, Sheng; Li, Wei; Li, Xuemei; Zhang, Sunfu (Frontiers in Psychiatry, 2022)
Our case report describes a 45-year-old woman who suffered from limb edema for 2 months. We focused on tumor recurrence and other common potential diseases based on the pituitary adenoma history. However, none of the examinations showed any abnormality. Later, her continuous complaints about the family relationship and depressed mood came into sight, and a psychiatry consultation was arranged. Following that, she was diagnosed with major depressive disorder. After several days of Deanxit and tandospirone treatment, the patient's limb edema dramatically subsided. This is the first case of limb edema associated with depression. This highlights the importance of awareness of mental illness for non-psychiatrists, especially in patients with severe somatic symptoms, but with negative results.